Inkjet‐Printed, Coplanar Electrolyte‐Gated Organic Field‐Effect Transistors on Flexible Substrates: Fabrication, Modeling, and Applications in Biodetection. Issue 2 (6th October 2022) - Chennit, Khalil; Delavari, Najmeh; Mekhmoukhen, Samia; Boukraa, Rassen; Fillaud, Laure; Zrig, Samia; Battaglini, Nicolas; Piro, Benoît; Noël, Vincent; Zozoulenko, Igor; Mattana, Giorgio
Abstract: The first example of inkjet‐printed, electrolyte‐gated organic field‐effect transistors, fabricated on flexible polyimide substrates is presented. The interdigitated source and drain electrodes, and the coplanar gate electrodes, are inkjet‐printed using a homemade gold nanoparticle ink. A semiconducting ink based on the p‐type, organic semiconductor poly[2, 5‐(2‐octyldodecyl)‐3, 6‐diketopyrrolopyrrole‐alt‐5, 5‐(2, 5‐di(thien‐2‐yl)thieno [3, 2‐b] thiophene)] (DPP‐DTT) is formulated and inkjet‐printed onto the channel. The performances of inkjet‐printed, coplanar devices are compared to those of transistors whose gate electrode consists in a metallic wire inserted in the electrolyte. Printed transistors show excellent electrical properties with field‐effect mobility as high as 0.04 cm 2 V −1 s −1 . The electrical behavior of inkjet‐printed, coplanar devices is also modeled using the Nernst–Planck–Poisson (NPP) equations, where the output and transfer curves are calculated based on the charge and potential distribution inside the device. Good quantitative agreement between the simulation and experiments is achieved, outlining the attainable use of NPP simulations as predictive tools for device design and optimization. To demonstrate an example of application, printed transistors are functionalized for the detection of complementary DNA strands. This study opens an avenue for the next generation of low‐cost, flexible sensors and circuits, both through experimental studies and device modeling. Abstract : The first example of coplanar, inkjet‐printed EGOFETs fabricated on flexible substrates is presented; their electrical behavior is modeled using a finite element approach based on the Nernst–Plank–Poisson equations. Good qualitative and quantitative agreement between experiments and simulations is achieved. Gate functionalization strategy is employed to make the printed EGOFETs able to detect complementary DNA strands in the electrolyte.